Quantitative Analysis of the Relationship between Blood Vessel Wall Constituents and Viscoelastic Properties: Dynamic Biomechanical and Structural In Vitro Studies in Aorta and Carotid Arteries. (9th April 2014) - Bia, Daniel; Zócalo, Yanina; Cabrera-Fischer, Edmundo I.; Wray, Sandra; Armentano, Ricardo L.
Abstract : The purposes of this work were to perform in sheep a quantification of the elastic, viscous, and inertial moduli obtained in carotid and aortic artery segments during in vitro dynamic studies that mimic the normal circulatory function; a quantitative determination of collagen, elastin, and vascular smooth muscle of the carotid and aortic segments analyzed in vitro ; the correlation between the amounts of each arterial wall constituent and the viscoelastic properties. To this end, nine healthy sheep were included. One artery was selected from each animal to evaluate its biomechanical properties: (a) in three sheep the ascending aorta, (b) in three the thoracic descending aorta, and (c) in the remaining three the proximal segments of the carotid artery. Each selected artery was instrumented with pressure and diameter sensors. After excision, a small ring-shaped sample was set apart from each segment for histological analysis. In conclusion, (a) the arterial compliance showed a positive association with the absolute and relative amount of the parietal elastin, and (b) arterial viscosity was positively associated with the relative amount of smooth muscle, and this association was increased when the correlation was calculated considering the amount of collagen as well as the amount of smooth muscle.